Interactions of Microbial Inoculations with Fertilization Options and Crop Establishment Methods on Modulation of Soil Microbial Properties and Productivity of Rice - Shahne, Amit Anil; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2024)
A field investigation was undertaken to assess the interactive effects of different crop establishment methods (CEMs) and microbial formulations in field conditions. The two year experiment was carried out in kharif season (June to October) of both 2013–14 and 2014–15 at Research Farm of ICAR-Indian Agricultural Research Institute, New Delhi India. The CEMs studied consist of puddled transplanted rice (PTR), system of rice intensification (SRI) and aerobic rice system (ARS); while microbial formulations consist of Anabaena sp. (CR1)+Providencia sp. (PR3) consortium (MC1) and Anabaena–Pseudomonas biofilm formulation (MC2). The microbial inoculation was applied with 75% recommended dose of nutrients (RDN) (90 kg nitrogen ha-1 and 19.35 kg phosphorus ha-1) and compared with 100% RDN. Soil microbiological properties showed significantly higher values in SRI in the first year; while in the second year, SRI and PTR remained on par and superior to ARS. Among the combinations of nutrient supplements, application of Anabaena–Pseudomonas biofilm formulation (MC2) with 75% RDN was superior in terms of all microbiological attributes studied [acetylene reduction activity (ARA), soil chlorophyll, soil dehydrogenase activity, microbial biomass carbon and alkaline phosphatase activity]. Application of microbial inoculation led to an increase in milled rice yield from 230 to 240 kg ha-1. Among the different combinations of CEMs and inputs investigated the application of 75% RDN+MC2+zinc (Zn) (soil applied 5 kg Zn ha-1 through zinc sulphate heptahydrate) in SRI can be a judicious option to maximize rice yield and soil health.